2018
DOI: 10.1097/sga.0000000000000306
|View full text |Cite
|
Sign up to set email alerts
|

Fast-Track Recovery Program After Major Liver Resection

Abstract: The objective of this study was to compare fast-track (FT) recovery protocol with the conventional one in patients treated with major liver resection by evaluating perioperative morbidity, length of hospitalization, and readmission rate. Sixty-two patients suffering from malignant liver tumors were surgically treated from May 2012 to April 2014. After randomization, they were prospectively divided into two groups: Group A patients (n = 32) followed FT recovery protocol and Group B patients (n = 30) were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…107 Two studies focused on adolescents, 22 , 37 and one study included both adults and children. 84 Although older adults (>75 years) were included in some studies 52 , 60 , 62 they were not specifically identified as the target population in any of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…107 Two studies focused on adolescents, 22 , 37 and one study included both adults and children. 84 Although older adults (>75 years) were included in some studies 52 , 60 , 62 they were not specifically identified as the target population in any of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Over half of studies involved interventions that were delivered during the preoperative phase of care (n=41, 48%); 13 studies delivered interventions during the intraoperative phase (n = 13, 15%); 24 , 26 , 31 , 43 , 46 , 51 , 74 , 75 , 86 , 92 , 97 , 99 , 101 13 studies (15%) delivered interventions solely in the postoperative phase, 36 , 39 , 44 , 47 , 48 , 60 , 66 , 68 , 73 , 77 , 82 , 90 , 107 Supplementary file 3 ; eight studies (9%) were based on interventions that were delivered during multiple phases of the perioperative pathway. 34 , 35 , 42 , 56 , 61 , 76 , 85 , 96 Almost half of the included studies assessed outcomes at multiple phases of the perioperative pathway (n = 34, 40%), whilst 24 studies (28%) assessed postoperative outcomes extending beyond the immediate PACU phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it is important to note a growing number of recently published trials, including randomized prospective studies, that confirm there is a place for ERAS in this surgical discipline. Although mentioned trials do not have an overwhelming number of subjects (62 patients in Kapritsou et al study [ 36 ]; 160 in Qi et al RCT [ 37 ]), they provide strong evidence of clinical safety and efficacy, even in major resections.…”
Section: Eras In Different Surgical Disciplinesmentioning
confidence: 99%